Efektifitas Model Research Based Learning Sebagai Upaya Meningkatkan Kualitas Pembelajaran Manajemen Investasi - Innaya Sari Melati; Wulan Suci Ramadhani (Ekspektasi: Jurnal Pendidikan Ekonomi, 2016)
This study aims to determine differences in teaching quality improvement Investment Management in students which use the model of Research Based Learning (RBL) and conventional learning. The study method is true experiment which is equipped with a qualitative approach to interpret the results. The population was Accounting Education students who take courses Investment Management. Samples of two classes selected by cluster random sampling. Data obtained by the testing techniques (early) and filling out the questionnaire, being the data analyzed by descriptive analysis and independent t test. Before, the data were analyzed by normality test, homogeneity test, and the similarity of initial competence test. The results revealed that there are differences in the quality of learning of Investment Management at the lectures with RBL model and the conventional one.